Operational risk management under Basel ll - A case of UAE banks - Tawalandana, Nilani (2010)
This thesis examines the ORM process in UAE banks in the light of Basel II Accord. The research also dwells into the concept of operational risk management with detailed study of the nature and characteristics of operational risk. The thesis studies the effects operational risk in the banking industry and shows that if not managed or controlled this risk can cause havoc to the organization. Operational risk management is an ongoing process and the banks need to develop and implement procedures and systems and evolve these systems to adapt to changes in the environment. This research studies the ORM framework of UAE banks with the help of a survey that was answered by the Risk Managers of various banks. The research gives information regarding the ORM processes in these banks and the various methods and tools used for the process. The research provides in depth study of ORM process in UAE banks and helps in assessing the efficacy of the programme.